The pathways from mother's love to baby's future - Korosi, Aniko; Baram, Tallie Z. (Frontiers in Behavioral Neuroscience, 2009)
Together with genetic factors, early-life experience governs the expression and function of stress-related genes throughout life. This, in turn, contributes to either resilience or vulnerability to depression and to aging-related cognitive decline. In humans and animal models, both the quality and quantity of early-life maternal care has been shown to be a predominant signal triggering bi-directional and enduring changes in expression profiles of genes including glucocorticoids and corticotropin releasing factor (CRH; hypothalamic and hippocampal), associated with the development of resilient or vulnerable phenotypes. However, many crucial questions remain unresolved. For examples, how is the maternal-derived signal transmitted to specific neuronal populations where enduring (likely epigenetic) regulation of gene expression takes place? What is the nature of this information? In other words, how do neurons know to ‘turn on’ epigenetic machinery? What are the direct functional consequences of altered gene expression? This review describes the voyage of recurrent bursts of sensory input from the mother (‘mother's love’) to CRH-expressing hypothalamic neurons that govern the magnitude of the response to stress. In addition, the acute and enduring effects of both nurturing and fragmented maternal care on the structure, cellular signaling and function of specific hippocampal and hypothalamic neurons are discussed. The evolving understanding of the processes initiated by the early life experience of ‘mother's love’ suggest novel molecular targets for prevention and therapy of stress-related affective and cognitive disorders.